Metaphors used in headlines of some electronic articles on US presidential election campaign 2012: A study from cognitive perspective - Nguyễn, Thị Thu Hằng (ĐHNN, 2017)
This MA minor thesis investigates the use of metaphors in headlines of some electronic articles on US presidential election campaign 2012. As the study applied the theoretical framework proposed by Lakoff and Johnson (1980), all three kinds of metaphors including structural, orientational, and ontological metaphors were found in 75 news headlines. Among 85 metaphorical expressions discovered in 75 article headlines, 67 were labeled as structural metaphors, making up 78.8%. It turned out that war terms appeared with the highest frequency among other source domains like sport competition, race, game, and business. While orientational metaphors were realized through 10 metaphorical expressions (corresponding to 11.8%), ontological metaphors were depicted in only 8 (equivalent to 9.4%). By analyzing how three kinds of metaphors employed in such political news headlines, the study is expected to partly reveal the conceptual frame of American people towards politics in general and election news in particular.